STUDENTS’ CRITICAL THINKING AT INFORMAL DEDUCTION LEVEL IN PISA-LIKE PROBLEMS ON SPACE AND SHAPE CONTENT - Aini, Afifah Nur; Nikmatuzzahro, Alfina (Jurnal Math-UMB.EDU, 2025)
Critical thinking is a person's ability to recognize, analyze, and solve problems. Indicators of critical thinking are focus, reason, inference, situation, clarity, and overview. This study was conducted to determine the critical thinking ability of students with the Informal Deduction thinking level in solving PISA-like problems on the content of space and shape on the material of Circles. This research is a qualitative descriptive study with subjects of grade XI students of Madrasah Aliyah at Jember. The instruments used were the Van Hiele Geometry Test (VHGT), PISA-like problems, and interview guidelines. Data analysis included data reduction, data presentation, and conclusion. Data validity was carried out through triangulation of techniques and sources. In the initial stage, VHGT was carried out on 26 students to determine their level of thinking. Then 2 students were selected at the Informal Deduction Level who have high mathematical ability and good communication. Next, a test was carried out to determine their critical thinking abilities. The results of the data analysis showed that students with the informal deduction thinking level were able to focus, reason, inference, situation, clarity, and overview. Keywords: Critical thinking, Van Hiele Thinking Level, PISA-like problem